Nutrient removal in pilot and full scale constructed wetland,putrajaya city,malaysia - Sim, Cheng Hua; Yusoff, Mohd Kamil; Shutes, Brian; Ho, Sinn Chye; Mansor, Mashhor (Elsevier, 2008)
Putrajaya Wetlands in Malaysia, a 200 ha constructed wetland system consisting of 24 cells, was created in 1997–1998 to treat surface runoff caused by development and agricultural activities from an upstream catchment before entering Putrajaya Lake (400 ha). It was designed for stormwater treatment, flood control and amenity use. The water quality improvement performance of a section of the wetland cells is described. The nutrient removal performance was 82.11% for total nitrogen, 70.73% for nitrate–nitrogen and 84.32% for phosphate, respectively, along six wetland cells from Upper North UN6 to UN1 from April to December 2004.